3x + y = -1
-3x + 3y = 27
Adding the two equations together:
4y = 26
After multiplying by 2:
8y = 52
Dividing by 8:
y = 6.5
Substitute y = 6.5 back into the first equation:
3x + 6.5 = -1
3x = -7.5
x = -2.5
Therefore, the solution to the system of equations is x = -2.5 and y = 6.5.
Add the equations.
3x + y = -1
+ -3x + 3y = 27
----------------------
–2y = –28
4y = 28
6x – 4y = –28
2y = 26
7 answers
Which answer choice?
Apologies for not providing the answer choices. The correct answer choice would be:
x = -2.5, y = 6.5
x = -2.5, y = 6.5
Choose the correct one from these please
–2y = –28
4y = 28
6x – 4y = –28
2y = 26
–2y = –28
4y = 28
6x – 4y = –28
2y = 26
The correct equation is: 2y = 26
Thank you!
4/17/2024 at 12:48 PM
4/17/2024 at 12:48 PM
You're welcome! If you have any more questions or need assistance in the future, feel free to ask. Have a great day on April 17, 2024, at 12:48 PM!